2010
DOI: 10.1063/1.3480981
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the photophysical properties of organometallic complexes to small chemical changes

Abstract: We investigate an effective model Hamiltonian for organometallic complexes that are widely used in optoelectronic devices. The two most important parameters in the model are J, the effective exchange interaction between the π and π∗ orbitals of the ligands, and ε∗, the renormalized energy gap between the highest occupied orbitals on the metal and on the ligand. We find that the degree of metal-to-ligand charge transfer character of the lowest triplet state is strongly dependent on the ratio ε∗/J. ε∗ is purely … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…We study the excited states of two iridium(III) complexes with potential applications in organic light-emitting diodes: factris(2-phenylpyridyl)iridium(III) [Ir(ppy) 3 ] and fac-tris(1-methyl-5-phenyl-3-n-propyl- [1,2,4]triazolyl)iridium(III) [Ir(ptz) 3 ]. Herein we report calculations of the excited states of these complexes from time-dependent density functional theory (TDDFT) with the zeroth-order regular approximation (ZORA).…”
Section: Triazolyl)iridium(iii)mentioning
confidence: 99%
See 1 more Smart Citation
“…We study the excited states of two iridium(III) complexes with potential applications in organic light-emitting diodes: factris(2-phenylpyridyl)iridium(III) [Ir(ppy) 3 ] and fac-tris(1-methyl-5-phenyl-3-n-propyl- [1,2,4]triazolyl)iridium(III) [Ir(ptz) 3 ]. Herein we report calculations of the excited states of these complexes from time-dependent density functional theory (TDDFT) with the zeroth-order regular approximation (ZORA).…”
Section: Triazolyl)iridium(iii)mentioning
confidence: 99%
“…Phosphorescent materials are particularly desirable over fluorescent emitters due to their potential to harvest both singlet and triplet excitations generated in a device. [1,2] However, the development of efficient deep-blue phosphorescent emitters, which are required for full-colour OLED displays, [3][4][5][6] has remained a persistent problem since the field was established with the discovery of the green phosphorescent complex factris(2-phenylpyridyl)iridium(III) [Ir(ppy) 3 ; Figure 1 and Table 1]. [7] Fac-tris(1-methyl-5-phenyl-3-n-propyl- [1,2,4]…”
Section: Introductionmentioning
confidence: 99%
“…However, Jacko et al 40,173,205 have recently found that an additional dependence on the energy gap between T 1 and S 1 , which is also inverse square to leading order, arises from the details of the hybridisation between ligand centred and MLCT excitations required to form T 1 . Thus Jacko et al's 205 work predicts that the radiative rate of T 1 varies as the fourth power of the inverse of the energy gap between T 1 and S 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorescent materials are particularly desirable over fluorescent emitters due to their potential to harvest both singlet and triplet excitations generated in a device. 37,173 However, the development of efficient deep-blue phosphorescent emitters, which are required for full colour OLED displays, 19,51,73,191 has remained a persistent problem since the field was established with the discovery of the green phosphorescent complex fac-tris(2-phenylpyridine)iridium(III) [Ir(ppy) 3 ;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation